Reducing the discomfort in viewing 3D video with a prism device modified eye convergence. Issue 4 (April 2021) - Chen, Chien-Yu; Lin, Hsien-Chang; Wu, Pei-Jung; Chuang, Chih-Hao; Lin, Bor-Shyh; Lin, Ching-Huang
Abstract: A prism device is utilized in this study for modifying the eye convergence to reduce eye accommodation and enhance the comfort in viewing 3D video. Without changing the contents of 3D films, it aims to apply the myosis, convergence, and accommodation visual triad of eyeballs viewing near distance to not change the eyeball pupillary distance when viewing 3D films. Without convergence, the discomfort caused by intraocular muscle contraction when viewing near distance is reduced. Such an effect of a small prism lens is also proven in this study. When viewing 3D films with 1.0△ lenses, the physiological accommodation reaction of eyes would reduce (the right eye decreases 65% and the left eye decreases 70%), revealing the decreasing tension of intraocular muscle. The subjective psychological evaluation result also shows that viewing 3D images with small prism lenses could enhance the comfort. The evaluation of optical simulation, physiological reaction, and mental fatigue proves that the small prism lens proposed in this study could actually improve the comfort in viewing 3D films. Abstract : Accommodation, Convergence, Prism, Visual fatigue, Psychological evaluation.